Genome-wide analysis of the invasive fungal pathogen Neopestalotiopsis reveals high genomic diversity, effector repertoires, and the assessment of fungicide resistance risks - Tika B. Adhikari; Norman Muzhinji; Susmita Gaire; Prem B. Magar; Anju Pandey; Swarnalatha Moparthi; Frank J. Louws (PLoS ONE, 2026)
Neopestalotiopsis species (spp.) have recently emerged as major pathogens worldwide, causing leaf spot, fruit rot, and crown rot of strawberry, resulting in increased disease outbreaks and economic losses. Despite their increasing impact, there is a limited genomic resource for this pathogen group, constraining insights into pathogenic mechanisms and fungicide resistance. We conducted whole-genome sequencing of 50 Neopestalotiopsis strains from major strawberry production regions in North Carolina using the Illumina NovaSeq platform. The generated genome assemblies enabled comprehensive analyses of fungicide-resistance-associated mutations and the prediction of effector repertoires using signal-peptide screening, secretion filtering, and machine-learning-based approaches. Eight key fungicide target genes (β-tubulin, cytb , cyp51A , cyp51B , Bos1, and SDHI subunits ( sdhB/C/D ) were examined for putative resistance mutations. Phylogenomic analysis based on single orthologs from protein-coding regions and average nucleotide identity (ANI) matrices grouped the strains into two major lineages (Clades A and B) of Neopestalotiopsis rosae and a third distinct lineage (Clade C) comprising other Neopestalotiopsis spp. Between 879 and 895, CAZymes were predicted per genome, with glycoside hydrolases and auxiliary activity enzymes predominating in plant cell wall degradation. Effector prediction revealed between 87 and 95 putative secreted effectors, including many cysteine-rich proteins and species-specific candidates. Variation in target gene sequence analysis revealed benzimidazole resistance mediated by β-tubulin E198A/K and widespread QoI resistance associated with cytb G143A. The cyp 51 gene exhibited extensive polymorphism, particularly H147Y and N284H, while the L98H variant was rare. No resistance-associated mutations were detected in any SDHI- or Os-1-target genes. This study represents the first comprehensive genomic assessment of Neopestalotiopsis strains infecting strawberry in North Carolina, revealing substantial genomic diversity, various enzymes and effectors involved in host colonization, and mutations linked to resistance to benzimidazole, QoI, and DMI, but not SDHI fungicides. These findings provide a foundation for developing improved, sustainable fungicide-use and disease-management strategies.